Effect of oil palm fiber on some physical properties of porous asphalt / Tamalkhani Syammaun - Tamalkhani, Syammaun (2013)
The use of waste fibers has been developing in many ways to increase the performance properties of asphalt mixture. Efforts to create a green technology which is more environmentally friendly that can produce economic value is also a consideration in the utilization of waste materials. The objective of this study is to evaluate the effect of oil palm fiber (OPF) on some physical properties of porous asphalt. Using OPF as the alternative, an additive in porous asphalt is one of the potential paths to improving the service properties of porous asphalt. In this study, five different contents of fiber (1%, 2%, 3%, 4% and 5%) were used by weight of bitumen. Several laboratory tests, namely drain down, air void, air abrasion loss, water abrasion loss, resilient modulus and permeability were conducted to compare and determine the specimen’s performance. The performances of porous asphalt with respect to OPF additives were analysed and validated using standard statistical techniques such as regression analysis and analysis of variance (ANOVA). In general, the results showed that the addition of OPF has a significant effect on the properties of porous asphalt. With regard to the drain-down test, the mix with 2% to 5% OPF content performed better at 4%, 4.5% and 5% binder content. However, adding more OPF to the mixture increased the air void content. The specimens containing 2% and 3% fiber in both conditions (air abrasion and water abrasion) showed lower abrasion loss than the control specimens (no fiber). For any particular binder, the coefficient of permeability decreases as the binder content increases. In reference to the results of resilient modulus, the value increased between 2% and 3% OPF content, but the higher OPF content in the mixture decreased the indirect tensile value. From the observations, it was evident that the addition of OPF has the potential to improve performance of asphalt pavements and prevent binder drain down. It is also a continuation in creating a better environment and an alternative way in which to re-use waste materials.